Poverty and alienation in the teaching retirement experience (Praxis Educativa, 2024)
This paper seeks to explore in the capitalist society the labor relations and the emotional turmoil experienced by workers upon reaching retirement age. The concepts of poverty and alienation are examined through theories and interviews with retired teachers. Experiences of exclusion from the social and professional dynamics that shaped their lives and the stripping of worth and productive identity engendered by the hegemonic discourse are analyzed. Only by modifying this production logic as the guiding matrix can this cultural stigmatization be brought to an end.
Keywords: capitalism; teaching profession; retirement; social exclusion; social alienation